Clinical dental adhesive application: the influence on composite-enamel interface morphology - Matei, Ruxandra; Popescu, Mihai Raul; Suciu, Mircea; Rauten, Anne Marie (Romanian journal of morphology and embryology, 2014)
Although the adhesion phenomenon is crucial in achieving and maintaining a composite building on dental structure, this phenomenon is not completely understood. On the other hand, adhesion is dependent on the interface quality (the interface between enamel and adhesive). In this study, the authors approached the subject of the influence of adhesive clinical application on the composite-enamel interface, which was less investigated by the scientists. On intact extracted human teeth were prepared enamel areas, and then filled with light-curing composite. The teeth were sectioned and prepared for microscopic investigation, at 10×, 100× and 200× magnifications.